Computational Prediction of Ammonia-Borane Dehydrocoupling and Transfer Hydrogenation of Ketones and Imines Catalyzed by SCS Nickel Pincer Complexes - Qiu, Bing; Wang, Wan; Yang, Xinzheng (Frontiers in Chemistry, 2019)
Inspired by the catalytic mechanism and active site structure of lactate racemase, three scorpion-like SCS nickel pincer complexes were proposed as potential catalysts for transfer hydrogenation of ketones and imines with ammonia-borane (AB) as the hydrogen source. Density functional theory calculations reveal a stepwise hydride and proton transfer mechanism for the dehydrocoupling of AB and hydrogenation of N-methylacetonimine, and a concerted proton-coupled hydride transfer process for hydrogenation of acetone, acetophenone, and 3-methyl-2-butanone. Among all proposed Ni complexes, the one with symmetric NH2 group on both arms of the SCS pincer ligand has the lowest free energy barrier of 15.0 kcal/mol for dehydrogenation of AB, as well as total free energy barriers of 17.8, 18.2, 18.0, and 18.6 kcal/mol for hydrogenation of acetone, N-methylacetonimine, acetophenone, and 3-methyl-2-butanone, respectively.